Remote sensing and GIS-based land assessment in Zhanaarka region of Ulytau oblast, Kazakhstan - Shokparova, Dana K.; Sirazhitdinova, Mukhabat; Bissenbayeva, Sanim B.; Patel, Nilanchal (Frontiers in Environmental Science, 2025)
Agricultural practices in Kazakhstan exert considerable pressure on the landscape, leading to environmental degradation, pastureland fragmentation, and biodiversity loss. Sustainable land management is crucial for balancing economic development and ecological preservation. This study assesses land conditions in the Zhanaarka region of Ulytau Oblast, Kazakhstan, focusing on climatic and anthropogenic impacts. Using Landsat 5 and 8 satellite imagery (2009, 2013, 2018), we evaluated land cover changes through NDVI analysis, climate factor assessment (temperature and precipitation), and GIS-based mapping. Pearson’s correlation and multivariate analysis were applied to identify relationships between vegetation dynamics and climatic variables, alongside anthropogenic influences such as land development and irrigation. Significant shifts in vegetation cover and land boundaries were observed over the study period. Multivariate analysis revealed no single climatic variable (temperature or precipitation) as a limiting factor for Normalized difference vegetation index (NDVI) changes. However, anthropogenic activities, including unsustainable land use, were key drivers of pasture degradation. The findings highlight the dominant role of human activities in land degradation, despite the region’s climatic vulnerabilities. The study underscores the need for integrated land-use policies to mitigate degradation and promote sustainable agricultural practices. Recommendations are provided to enhance resilience against climate change and anthropogenic pressures.